Honey from Stingless Bee as Indicator of Contamination with Metals - Nascimento, Andreia Santos do; Chambó, Emerson Dechechi; Oliveira, Daiane De Jesus; Andrade, Brunelle Ramos; Bonsucesso, Josemario Santana; Lopes de Carvalho, Carlos Alfredo (Sociobiology (Chico, CA), 2018)
Melipona scutellaris (Apidae, Meliponini) is one of the main species of stingless bees used in beekeeping in the Northeast of Brazil. We examined the honey from M. scutellaris as an indicator to evaluate the levels of metals at sampling sites subject to a broad spectrum of environmental pollutants. The collections were carried out in the urban-industrial area of Salvador, Bahia and the metropolitan region. Samples (n= 58) were submitted to the nitroperchloric digestion procedure. We used the inductively coupled plasma optical emission spectrometry technique (ICP OES) to determine the concentration of metals (Cd, Co, Cr, Cu, Fe, Mn, Mo, Ni, Pb and Zn) in the samples. The studied metals were detected among the samples, which presented tolerable levels according to current Brazilian legislation and recommendations from the World Health Organization (WHO), except for Cr, which presented mean values higher than the threshold for all sampling sites. The detection of the analyzed metals indicates that the honey of M. scutellaris is a useful tool to evaluate the presence of environmental contaminants; therefore, it can be considered a good indicator of environmental contamination for monitoring a particular region and preventing issues due to the release of metals into the environment.